Short Sleep Duration Is Associated with Higher Energy Intake and Expenditure among African-American and Non-Hispanic White Adults. Issue 4 (12th February 2014) - Patterson, Ruth E.; Emond, Jennifer A.; Natarajan, Loki; Wesseling-Perry, Katherine; Kolonel, Laurence N.; Jardack, Patricia; Ancoli-Israel, Sonia; Arab, Lenore
Abstract: Habitual short sleep duration appears to increase the risk of obesity. The objective of this paper is to investigate the association of habitual sleep duration with objective measures of energy balance. One hundred twelve African-American and 111 non-Hispanic whites aged 21–69 y participated in a cross-sectional study of dietary assessment and biomarkers. Participants reported the mean number of hours per day spent sleeping over the past year. Short sleep duration was defined as ≤6 h/d of sleep. Energy intake (kilocalories) was objectively assessed using the 2-point doubly labeled water technique to determine total energy expenditure, which is approximately equal to energy intake. Physical activity energy expenditure (kilocalories) was estimated as total energy expenditure minus each participant's calculated basal metabolic rate and the thermogenic effect of food. Compared with participants who slept ≤6 h, individuals who slept 8 h were significantly less likely to be obese (OR: 0.33; 95% CI: 0.14, 0.79). However, this association was not linear across 6–9 h of sleep ( P -trend = 0.16). There was an inverse association between sleep and energy intake ( P -trend = 0.07): compared with ≤6 h/d, adults who reported ≥9 h sleep consumed 178 fewer kcal/d. There was also an inverse association between sleep and physical activity ( P -trend = 0.05): compared with ≤6 h/d of sleep, adults who reported 9 h of usual sleep expended 113 fewer kcal/d in physical activity. These data indicate that, compared with longer sleep duration, adults who report habitual short sleep duration have somewhat higher physical activity energy expenditure but considerably higher energy intake. Habitual short sleep duration appears to be 1 of the facets of modern life leading to a mismatch between energy intake and physical activity.